PENYULUHAN DAN PENANAMAN BIBIT MANGROVE DALAM MENUNJANG EKOWISATA BAHARI MENUJU EKONOMI BIRU DI KECAMATAN BINUANG - Irma Yulia Madjid; Muhammad Takril; Fajriani Fajriani (Universitas Mataram, 2023)
Sustainable mangrove management is crucial in environments that have been threatened by damage. Mangrove management can also be utilized as a potential ecotourism asset beneficial to the community, particularly in the Binuang District of Polewali Mandar Regency. This community service activity aims to provide education about the importance of preserving coastal ecosystems, especially mangroves. It also aims to impart knowledge to students and the community about mangrove planting techniques, raise awareness among the community to pay more attention to the environment and ecosystem conservation. One of the ways to achieve this is through activities that contribute to preserving the balance of the mangrove ecosystem. The method employed in this community service activity is the extension method, involving the delivery of materials and direct discussions with the local community, followed by the actual planting of mangrove seedlings in locations that show signs of damage. The outcomes of this community service include broadening the local community's perspective and fostering an awareness of the significance of mangroves for various aspects of organisms' lives. From this community service activity, it can be concluded that it is crucial to preserve coastal ecosystems, especially mangroves, and there is a need for knowledge about mangrove planting techniques. Building community awareness about the importance of preserving and maintaining mangrove conservation areas, which serve as habitats for other marine organisms, is essential. It is hoped that the community will continue these mangrove planting activities to ensure sustainability for the future